Characterization and Quantification of the Compounds of the Ethanolic Extract from Caesalpinia ferrea Stem Bark and Evaluation of Their Mutagenic Activity - Wyrepkowski, Carlos Cesar [UNESP]; Maldonado Gomes da Costa, Daryne Lu [UNESP]; Sinhorin, Adilson Paulo; Vilegas, Wagner [UNESP]; De Grandis, Rone Aparecido [UNESP]; Resende, Flavia Aparecida [UNESP]; Varanda, Eliana Aparecida [UNESP]; Santos, Lourdes Campaner dos [UNESP] (Mdpi Ag, 2014)
Caesalpinia ferrea Martius has traditionally been used in Brazil for many medicinal purposes, such as the treatment of bronchitis, diabetes and wounds. Despite its use as a medicinal plant, there is still no data regarding the genotoxic effect of the stem bark. This present work aims to assess the qualitative and quantitative profiles of the ethanolic extract from the stem bark of C. ferrea and to evaluate its mutagenic activity, using a Salmonella/microsome assay for this species. As a result, a total of twenty compounds were identified by Flow Injection Analysis Electrospray Ionization Ion Trap Mass Spectrometry (FIA-ESI-IT-MS/MSn) in the ethanolic extract from the stem bark of C. ferrea. Hydrolyzable tannins predominated, principally gallic acid derivatives. The HPLC-DAD method was developed for rapid quantification of six gallic acid compounds and ellagic acid derivatives. C. ferrea is widely used in Brazil, and the absence of any mutagenic effect in the Salmonella/microsome assay is important for pharmacological purposes and the safe use of this plant.
Keywords: Caesalpinia ferrea; HPLC-DAD quantification; HPLC/ESI-IT-MS; hydrolyzable tannins; mutagenic activity